Elevation and Volume Changes in Greenland Ice Sheet From 2010 to 2019 Derived From Altimetry Data - Chen, Guodong; Zhang, Shengjun; Liang, Shenghao; Zhu, Jiaheng (Frontiers in Earth Science, 2021)
Long-term altimetry data are one of the major sources to analyze the change in global ice reserves. This study focuses on the elevation and volume changes in the Greenland ice sheet (GrIS) from 2010 to 2019 derived from altimetry observations. In this study, the methods for determining surface elevation change rates are discussed, and specific strategies are designed. A new elevation difference method is proposed for CryoSat-2 synthetic aperture interferometric (SARin) mode observations. Through validation with Airborne Topographic Mapper (ATM) data, this new method is proved to be effective for slope terrains at the margins of the ice sheet. Meanwhile, a surface fit method is applied for the flat interior of the ice sheet where low resolution mode (LRM) observations are provided. The results of elevation change rates in the GrIS from 2010 to 2019 are eventually calculated by combining CryoSat-2 and ATM observations. An elevation change rate of −11.83 ± 1.14 cm·a−1 is revealed, corresponding to a volume change rate of −200.22 ± 18.26 km3·a−1. The results are compared with the elevation changes determined by Ice, Cloud, and Land Elevation Satellite (ICESat) from 2003 to 2009. Our results show that the overall volume change rate in the GrIS slowed down by approximately 10% during the past decade, and that the main contributor of GrIS ice loss has shifted from the southeast coast to the west margin of the ice sheet.